(untitled) (European journal of volunteering and community-based projects, 2021)
This paper examines the interactive relationships between international tourism, economic growth and environmental quality in three countries of North Africa (Tunisia, Maroc, Egypt) over the period 1981 -2019 . The study used the ARDL model. The results show that tourism has a direct and statistically significant impact on the level of carbon dioxide ) emissions (CO2) and economic growth in the long run. The results also confirm the existence of an inverted U-shaped relationship for Morocco and Egypt between CO2 emissions and income level, while this relationship takes the form of a U- shaped in Tunisia. The error correction models in this study have shown that : (1) CO2 emissions converge towards their long-term equilibrium situation with a speed of the order of 5.8% in Morocco , 20% in Egypt and 27.9% in Tunisia through economic growth channels , of the consumption of energy and tourism. This finding reveals that the growth of tourism allows significantly , climate change to move to higher levels. (2) economic growth converges towards its long-term equilibrium by an adjustment speed of the order of 25.7% in Morocco, 5.8% in Egypt and 2.1% in Tunisia.